GROWTH AND YIELD OF FODDER PEARL MILLET (Pennisetum glacum L.) GENOTYPES AS INFLUENCED BY NITROGEN LEVELS UNDER RAINFED CONDITION - M. ANURADHA, R. SUSHEELA, M. SHANTI, T. SHASHIKALA, V. CHANDRIKA and (The Journal of Research, PJTSAU, 2017)
Area under fodder crops in India is around 8.6 m ha and to meet the fodder shortage for growing animal population, the fodder growing area should ideally be 20 m ha, by 2020 AD. However, this appears to be rather difficult to achieve because of preferential food need for human beings(Hazra and Tripathi, 1998).Therefore productivity is to be through agronomic manipulation. Pearlmillet (Pennisetum glaucum L.) is one of the most widely adopted cerealforage crops under rainfed condition and gaining more popularity due to its quick growing habit, high quality forage and better palatability. Nitrogen is an essential primary nutrient for profuse plant growth and plays a pivotal role in production of forage crops. The application of nitrogen at various growth stages is one of the ways to increase the productivity of forage crops. Recently many new improved varieties of pearlmillet are coming up as forage varieties and need to standardize the dose of nitrogen for better forage  yield and quality. Therefore, a field trial was conducted to find out the fodder production potential and nutritional quality of different fodder pearlmillet genotypes grown under different levels of nitrogen application in rainfed condition.